Pengaruh Sistem Pengendalian Intern (SPI) Kepatuhan Pada Peraturan Perundang-Undangan Standar Akuntansi Pemerintahan (SAP) dan Kecukupan Pengungkapan terhadap Opini Audit Atas Laporan Keuangan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
This study aims to determine the effect of the Internal Control System (ICS), Regulatory Compliance Legislation, Government Accounting Standards (GAS), and Adequacy of Disclosure Against Audit Opinion. The data collection is done by providing as many as 49 copies of the questionnaire, but only 39 questionnaires can be analyzed and processed. The questionnaires were distributed to the auditor who works remain in BPK RI Representative of East Kalimantan. The analytical tool used in this study using Partial Least Square (PLS). The results showed that the Internal Control System (ICS) and Compliance Regulation Legislation does not affect and negatively affect audit opinion, while the Government Accounting Standards (GAS) and Adequacy of Disclosure positive and significant impact on the audit opinion.Keywords: Internal Control System (ICS)